ANALISIS PRESTASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN IPAS DITINJAU DARI AKTIVITAS BELAJAR KELAS V SEKOLAH DASAR - Eka Wulandari; Eko Kuntarto; Issaura Sherly Pamela (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to identify the types of students' learning activities, analyze the levels of learning activities, and analyze students' learning achievements in science lessons in terms of learning activities. This research was conducted at SDN 111/I Muara Bulian, involving one teacher and 28 class V students. This research adopts a qualitative approach with a case study type of research. Research data was obtained through observations of the learning process in science subjects, interviews with the teacher and three class V students, and assessment of students' test results. Data analysis was carried out using thematic analysis techniques. The research results show that students' learning activities in class consist of 8 types, namely visual, oral, listening, writing, drawing, motoric, mental and emotional activities. Learning activities carried out by students have different percentage levels. Based on the results of observations, it is known that there are students who have met the learning activity indicators, but there are also students who have not met the indicator criteria so that visual activities obtained a percentage of 78.6%, oral activities 69%, listening activities 79.7%, writing activities 85.7%, drawing activities 75%, motor activities 77.5%, mental activities 67.9%, and emotional activities 67.8%. The learning achievements achieved by each student also vary. Students who are actively involved in the learning process get satisfactory learning achievements while students who are passive get unsatisfactory learning achievements. So, these learning activities influence the learning achievements obtained by students at the end of each lesson. This research provides a deeper understanding of learning achievement in terms of learning activities in science subjects. The results of the research can support student involvement in the learning process in science subjects so that student learning achievement can improve well.